Arsenic : Natural and Anthropogenic. - Deschamps, Eleonora (Arsenic in the environment., 2011)
The discussion on arsenic in the environment is complex and must grasp the importance of very many, mostly unrelated works on individual aspects. This volume represents one of the first comprehensive and interdisciplinary examinations into arsenic's behaviour in air, water, soils, sediments, plants and the human body. Based on state-of-the-art investigations into the global arsenic cycle, the related human toxicology and available remediation technologies, arsenic is assessed holistically in all the environmental compartments. Using the results of primary research, the authors offer concrete s.